Desnaturação de oxihemoglobinas humanas A, A2 e S pelo metodo de tampão isopropanol - Naoum, P. C.; Teixeira, U. A.; Machado, P. E. de Abreu; Michelin, O. C. (My University, 1978)
Human oxyhaemoglobin A and A2 from normal individuals and oxyhaemoglobin S from patients with sickle cell anaemia and sickle cell trait were studied using Isopropanol/buffer method at 37°C and 40°C. Hb S was less stable than Hb A, whereas Hb A2 was considerably more stable than either. Denaturation of Hb S was dependent on temperature and its concentration. Between the patients with sickle cell trait it was not possible to verify the influence of the concentration probably due to the small range used (from 38% to 44%).
The denaturation of human oxyhaemoglobin A, A2 and S by isopropanol/buffer method
Keywords: 2 propanol; hemoglobin a; hemoglobin a2; blood and hemopoietic system; human cell; sickle cell anemia; sickle cell trait; 1-Propanol; Blood Protein Electrophoresis; Buffers; Heat; Hemoglobin A; Hemoglobin A2; Hemoglobin, Sickle; Human; Oxyhemoglobins; Protein Denaturation